Analisis Tingginya Tingkat Perceraian di Kota Medan - Maria Ferba Editya Simanjuntak; Rayani Saragih (PERSPEKTIF, 2022)
This study aims to find out what are the causes of divorce in the people of Medan City, as well as to analyze the highest cause of divorce filed at the Medan City Religious Court. This study focuses on the background analysis of divorce in the Medan City Religious Court. This research is a social research using qualitative research methods that can produce descriptive data in the form of written words, either from the data of the Religious Courts or from the oral staff of the Medan City Religious Courts. Penelitian ini menggunakan pendekatan naturalistik dengan wawancara (depth interview) sebagai metode pengumpulan data. Research informants were determined by snowball among widows and widowers in the Medan City area who were divorced throughout 2021 and from the Religious Courts. Data analysis and interpretation refers to the six steps of analysis as stated by Creswell. And this study concludes that in 2021 the registration of Divorce in the Religious Courts decreased due to restrictions on working hours and PPKM.